2017
DOI: 10.1080/07317115.2017.1322162
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Tablet Technology by Older Adults in Health Care Settings—Is It Effective and Satisfying? A Systematic Review and Meta Analysis

Abstract: Clinicians should be encouraged to utilize tablet technology in the care of older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…One area that has attracted interest is the use of technology by older adults in various health settings, both in formal health care [11,12] and from salutogenic perspectives [13,14] targeting social isolation and participation. However, there is a strong need to find evidence of the effectiveness and efficiency of health technology interventions, which is becoming increasingly important as the number of available health technology solutions grows [15].…”
Section: Introductionmentioning
confidence: 99%
“…One area that has attracted interest is the use of technology by older adults in various health settings, both in formal health care [11,12] and from salutogenic perspectives [13,14] targeting social isolation and participation. However, there is a strong need to find evidence of the effectiveness and efficiency of health technology interventions, which is becoming increasingly important as the number of available health technology solutions grows [15].…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of information technology electronic devices, such as tablets, in the context of primary care consultations for older adults is not yet well understood [11]. A systematic review and meta-analysis suggested older adults have the potential to benefit from the use of tablet technology, especially in health care settings [12]. Information technology can be used in different ways to promote health literacy among people with low literacy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the wide range of studies available, there is a visible lack of research, especially randomized controlled trials with study interventions, to test the effectiveness of the photo story for increasing health-related understanding and the usefulness of electronic devices, such as tablets [12]. A systematic review assessing the evidence for the effectiveness of such interventions concluded that there is a lack of consistent evidence for effective interventions [16].…”
Section: Introductionmentioning
confidence: 99%
“…The suggestion from one study participant for a government algorithm [27], presumably available online, that could be used to calculate the duration of needed sun-exposure after the entry of variables such as gender and age, deserves consideration. There is research that suggests older adults will consider using technology to improve communication and health [44,45], and thus whether technological tools could improve vitamin D nutritional education and interventions to improve status in older adults warrants exploration.…”
Section: Discussionmentioning
confidence: 99%